ICU Admission Preferences in the Hypothetical Event of Acute Critical Illness: A Survey of Very Old Norwegians and Their Next-of-Kins - Gabriele Leonie Schwarz, MD; Elisabeth Skaar, MD, PhD; Ingrid Miljeteig, MD, PhD; Karl Ove Hufthammer, PhD; Karen E. A. Burns, MD, MSc, FRCPC; Reidar Kvåle, MD, PhD; Hans Flaatten, MD, PhD; Margrethe A. Schaufel, MD, PhD (Critical Care Explorations)
OBJECTIVES:. To explore older patients’ ICU admission preferences and their next-of-kins’ ability to predict these preferences. DESIGN:. Self-administered survey. SETTING:. Three outpatient clinics, urban tertiary teaching hospital, Norway. PATIENTS:. Purposive sample of outpatients 80 years old or older regarded as potential ICU candidates and their next-of-kins. INTERVENTIONS:. None. MEASUREMENTS AND MAIN RESULTS:. We asked about the patients’ ICU admission preferences in three hypothetical scenarios of acute critical illness. Next-of-kin respondents were asked to make a proxy statement regarding the older respondents’ wishes regarding ICU admission. For each treatment choice, all respondents could provide their level of confidence. Additionally, we sought to identify demographic and healthcare-related characteristics that potentially influenced ICU admission preferences and proxy accuracy. Of 202 outpatients 80 years old or older, equal proportions opted for (39%; CI, 33–45%) and against (40%; CI, 34–46%) ICU admission, and one in five (21%; CI, 17–26%) did not wish to engage decision-making. Male gender, religiosity, and prior ICU experience increased the likelihood of older respondents opting for ICU admission. Although next-of-kins’ proxy statements only weakly agreed with the older respondents’ true ICU admission preferences (52%; CI, 45–59%), they agreed with the next-of-kins’ own ICU admission preferences (79%; CI, 73–84%) to a significantly higher degree. Decisional confidence was high for both the older and the next-of-kin respondents. CONCLUSIONS:. In this purposive sample of Norwegian potential ICU candidates 80 years old or older, we found substantial variation in the ICU admission preferences of very old patients. The next-of-kins’ proxy statements did not align with the ICU admission preferences of the older respondents in half of the pairs, but next-of-kins’ and older respondents’ confidence levels in rendering these judgments were high.